MM*INDO : INTERACTIVE STATISTICS LEARNING IN INDONESIAN LANGUAGE - Hizir Sofyan; Noer Azam Achsani (STATISTIKA: Forum Teori dan Aplikasi Statistika, 2004)
In line with the development of computer and information technology, interactive learning become analternative choice to the conventional one. MM*Indo is an interactive introductory to the world of statistics usingIndonesian Language. This software would help the student to understand the statistic lectures, especially in theelementary phase, through it’s dynamic explanation and many practical exercises. The software is supported by the XploRestatistical programming language and written in HTML and Javascript, so that it can be executed via World Wide Web andalso CD-ROM. It consists of 12 chapter covering all introductory themas of statistics, from the descriptive statistics,introduction to the probability, hypothesis testing until linear regression.